Revealing the Metabolic Flexibility of “Candidatus Accumulibacter phosphatis” through Redox Cofactor Analysis and Metabolic Network Modeling - da Silva, Leonor Guedes; Gamez, Karel Olavarria; Gomes, Joana Castro; Akkermans, Kasper; Welles, Laurens; Abbas, Ben; Loosdrecht, Mark C.M.van; Wahl, Sebastian Aljoscha (Applied and Environmental Microbiology, 2020)
Environmental fluctuations in the availability of nutrients lead to intricate metabolic strategies. “Candidatus Accumulibacter phosphatis,” a polyphosphateaccumulating organism (PAO) responsible for enhanced biological phosphorus removal (EBPR) from wastewater treatment systems, is prevalent in aerobic/anaerobic environments. While the overall metabolic traits of these bacteria are well described, the nonavailability of isolates has led to controversial conclusions on the metabolic pathways used. In this study, we experimentally determined the redox cofactor preferences of different oxidoreductases in the central carbon metabolism of a highly enriched “Ca. Accumulibacter phosphatis” culture. Remarkably, we observed that the acetoacetyl coenzyme A reductase engaged in polyhydroxyalkanoate (PHA) synthesis is NADH preferring instead of showing the generally assumed NADPH dependency. This allows rethinking of the ecological role of PHA accumulation as a fermentation product under anaerobic conditions and not just a stress response. Based on previously published metaomics data and the results of enzymatic assays, a reduced central carbon metabolic network was constructed and used for simulating different metabolic operating modes. In particular, scenarios with different acetate-toglycogen consumption ratios were simulated, which demonstrated optima using different combinations of glycolysis, glyoxylate shunt, or branches of the tricarboxylic acid (TCA) cycle. Thus, optimal metabolic flux strategies will depend on the environment (acetate uptake) and on intracellular storage compound availability (polyphosphate/glycogen). This NADH-related metabolic flexibility is enabled by the NADH-driven PHA synthesis. It allows for maintaining metabolic activity under various environmental substrate conditions, with high carbon conservation and lower energetic costs than for NADPH-dependent PHA synthesis. Such (flexible) metabolic redox coupling can explain the competitiveness of PAOs under oxygen-fluctuating environments.
CRIS-Team Scopus Importer:2022-01-11
Keywords: central carbon metabolism; enhanced biological phosphorus removal; enzymatic assays; flux balance analysis; polyphosphate-accumulating organisms; redox cofactors; “Candidatus Accumulibacter phosphatis”